Summits, state visits and political networks: Bucharest's triangular relationship with Washington and London, 1974-80 - Hotea, Mihai (2024)
This thesis sheds new light on how Anglo-American leaders used summits as tools to obtain geopolitical goals, namely, to support Romania’s independent stance in foreign policy within the communist bloc. The study argues that after 1974, a triangular relationship was established between Romania, the US and the UK, via summits and state visits. Irrespective of the political stripe of the administration in America and Britain, close relations with Romania were maintained via high level meetings. The Anglo-American allies co-ordinated their policies towards Romania to encourage Bucharest’s independent foreign policy. Accordingly, Nicolae Ceaușescu became the first communist leader courted in meetings at the highest level in Washington and London. With regard to relations with Romania, geopolitical goals trumped concern for human rights throughout the entire period. The triangular relationship went into decline in 1980, as Ceaușescu no longer secured summits and state visits with US and UK leaders beyond this year. The thesis also investigates the substantive issues arising from this triangulation, such as co-operation on international affairs, emphasising that Romania played a key intermediary role in the midst of the Cold War between the US and the UK on the one hand, and other third parties, especially in the Middle East, on the other. The significance of trade to the triangular relationship was also significant and further incentivised Romania to pursue an independent foreign policy, although Britain and America remained economic competitors towards the country, particularly when it came to arms sales. Moreover, the thesis explores Romania’s foreign policy, showing that a small number of actors influenced it, while stressing that the regime internally was repressive and concentrated in Ceaușescu’s hands. Detailed evidence supporting the arguments of the thesis has been gathered from all three states, and the study has been informed by official documents, newspapers and memoir literature.